Avaliação dos riscos ambientais e ecotoxicológicos do reúso de águas residuárias em piscicultura - Gradvohl, Soraia Tavares de Souza (2006)
The concern regarding the quality and quantity of drinking water has encouraged the reuse of water as an alternative to tackle this problem. The reuse became therefore an important environmental management tool, aiming at freeing the water of better quality for more noble purposes. The reuse with application in fish farming is a low cost alternative source of protein production, in addition to functioning as a form of recycling nutrients. But the sustainability of this activity is directly related to the quality of treated wastewater and its effects on water quality in fish tanks. Another notable fact is the growing concern about the potential risks inherent in this activity. In this scenario, the need to conduct a deeper study of the risks inherent in the reuse of wastewater, both from an environmental approach as an ecotoxicological point of view. For this, acute toxicity tests were performed, of short duration, to evaluate the toxicity of treated and raw sewage from a sewage treatment plant to tertiary level, composed of a system of stabilization ponds, with the test organisms fish freshwater species Oreochromis niloticus (Nile tilapia). The tests aimed to determine the acute toxicity index (LC50). The treated effluent was used in two distinct stages, with fish older than 60 days and fingerlings with a life span less than 15 days. In both, no mortality was observed in any organism. In the case of raw sewage, the assay was performed with or without aeration, being obtained for the raw sewage without the LC50-24h aeration rates of 68.0% and 35.4% LC50-96h. However, with the applied mechanical aeration at two dilutions of 50 to 100% of raw sewage, the LC50's were found 44.5% (24 h), 41.0% (48 h) and 36.7% (96 h). The assay was also performed to evaluate the level of ammonia toxicity, given that the same has been considered by several researchers-toxic to algae, for zooplankton and fish. For these assays were determined LC50's of 2.01 mg / L NH3-N (2 H), 1.97 mg / L NH3-N (4 h) and 1.66 mg / L NH3-N (up to 96 h) . Furthermore, it was performed a test with ammonia nitrogen varying pH to give three different media - acid, basic and neutral - due to the influence of toxicity on the calculated index. The LC50's found in this case were: 8.70 mg / L for a time of 2 to 4 hours and 6.45 mg / L for 24, 48 and 96 hours for the acid medium; 8.70 mg / L for 2 hours and 6.45 mg / L for 4, 24, 48 and 96 hours for the neutral range; and 1.96 mg / L 2 hours onwards to the basic medium. Finally, a risk analysis methodology was used in order to carry out a study of the potential effects on human health and the environment, and also proposing measures to try to minimize the possible adverse impacts.